The politics of the heart: The history, evolution and success of a post-ideological political symbol. (1st June 2017) - Novelli, Edoardo
After a brief historical overview on the diffusion of the heart symbol and its meanings over the centuries in different cultures and civilizations, this article focuses on the last century, emphasizing that, in the early twentieth century in Western culture, the symbol of the heart retained a religious connotation and was totally alien to the iconographic lexicon of politics. The review of the political posters produced in the main Western and European countries reveals very few exceptions. The extensive iconographic output of the three main twentieth-century ideologies – fascism, nazism and communism – did not use the heart symbol, although they extensively employed visual communication and symbolic language. Its powerful religious meaning and appeal to sentiments like love and mutual support were irreconciliable with those of the three ideologies. The heart's absence from the political–symbolic repertoire continued even in the post-World War II era. The article points out that this symbol began to make its way into political iconography in the last twenty years of the previous century after the creation of the symbol 'I ♥ N.Y' in 1977. The great popularity of Milton Glaser's invention started a new life for the heart symbol. It acquired new values and meanings and became a symbol of pleasure, friendliness and empathy, in tune with the language and culture of advertising and consumer goods. From this point on, this symbol entered the visual vocabulary of a politics that was facing phenomena such as secularization and de-ideologization. Focusing then on recent Italian history, the article shows that the heart is widely present in the political posters of the so-called Second Republic, which officially started in 1994. The key Italian players of the new political season began to deploy the heart symbol in their visual vocabulary, not with traditional meanings but with new ones, trascending historical political groupings and the traditional left/right ideological axis. Through an extensive visual documentation of some of the most striking cases, the article shows how the use of the symbol of the heart in Italian political iconography continued in the years that followed, always characterized by little or no political meaning. In its final part, the article claims that the emotional trend in the candidates' and parties' communication, which found its highest expression in the use of the heart symbol, free of any political or manifesto-related content, is not confined to Italy. The analysis of posters produced in different countries documents how the political use of the heart symbol is now international, from north to south, from east to west, and common to different political alignments, from left to right. In conclusion, the article links the prevalence and great success of a post-ideological and emotive symbol such as the heart with some of the ongoing processes in modern mediatized public life and political communication.